Edición CRISPR/Cas9 del exón 2 del gen Msh1 para generar variabilidad en el genoma de los cloroplastos de trigo - Lencina, Franco Daniel; Beznec, Ailin; Faccio, Paula Daniela; Etchart, Valeria Juliana; Garcia, Araceli Nora; Landau, Alejandra Mabel; Bossio, Adrian Ezequiel (REDBIO, 2025)
Poster